Portal Vein Embolization for Future Liver Remnant Enhancement and Combined Modality Treatment for the Management of Post-hepatic Resection Biliary Fistula in an 18-Month Old Child With Hepatoblastoma - Kannappan, Odaiyappan; Keditsu, Keduovinuo; Bhagat, Monica; Shrimal, Anurag; Polnaya, Ashwin; Kulkarni, Suyash; Qureshi, Sajid S. (Frontiers in Surgery, 2019)
Hepatic resection is the mainstay of treatment for hepatoblastoma. However, the presence of adequate future liver remnant (FLR) is essential to prevent postoperative liver failure. Portal vein embolization (PVE) is commonly utilized in adults for promoting hypertrophy of FLR, however, it is sparingly used in children. Secondly, bile leak after liver resections is a well-defined complication. Apart from conservative treatment such as drainage and antibiotic, several management strategies including endoscopic, percutaneous and surgical approaches have been described for its management. We present an 18-month old child with hepatoblastoma for whom PVE was performed to enhance the FLR so that an extended right hepatectomy could be accomplished. The same patient endured delayed postoperative biliary leak wherein the conservative, and non-operative interventional procedure failed, however, surgery combined with intraoperative interventional radiology procedure was utilized with a favorable outcome.